2007
DOI: 10.1111/j.1440-1673.2007.01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Colour Doppler ultrasound evaluation of orbital vessels in diabetic retinopathy

Abstract: The aim of this study was to determine the role of colour Doppler imaging in the retrobulbar vascular circulation in diabetic retinopathy (DR). Maximum (V(max)), end-diastolic (V(min)) and average (V(mean)) velocities of blood flows and pulsatility index and resistivity index (RI) in central retinal artery (CRA), short branches of posterior ciliary artery (PCA) and ophthalmic artery of the 65 diabetic and 22 control eyes were measured. The CRA V(max) level in the control group was significantly higher than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…These studies focused only on some of the orbital vessels and measured indices and velocities in specific diabetic or control groups. They were usually of limited sample size, and the results produced were inconsistent [3][4][5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies focused only on some of the orbital vessels and measured indices and velocities in specific diabetic or control groups. They were usually of limited sample size, and the results produced were inconsistent [3][4][5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of hemodynamics in DR has not been clearly defined [2]. There have also been conflicting reports of impaired hemodynamics in the orbital vessels in patients with DR [3][4][5][6][7][8][9][10][11][12][13][14]. Orbital blood flow velocities were increased in some studies [3], but decreased in others [4, 9-11, 13, 14], or unchanged [15].…”
Section: Introductionmentioning
confidence: 99%
“…Color Doppler imaging is a noninvasive, reproducible, and easily applied technique, and it has been shown to be useful in evaluating hemodynamic changes in several orbital and retinal vascular diseases [18]. It has been reported that blood flow velocity in the CRA was decreased in rats with DR [14].…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] However, conflicting reports regarding impaired hemodynamics in the orbital vessels in patients with DR have emerged. Orbital blood flow velocities increased in some studies, 18 yet decreased in others 10,16,[19][20][21][22][23][24] or else remained unchanged. 25 Nevertheless, PPV for DR complications may affect ocular hemodynamics.…”
Section: Introductionmentioning
confidence: 98%